Apoloniusz z Tiany. Święty czy szarlatan? - GĘBURA, Krzysztof (Historia i Świat, 2014)
The present paper examines the life of Apollonius of Tyana, who lived in the Greek territory in the first century AD, a famous pagan Phytagorean philosopher and, allegedly, a man of numerous miracles. The text is divided into three parts. In the first one the sources of information about Apollonius are discussed. Many of them come from debates between pagan and Christian intellectuals, who lived after his death. The mostimportant testimony is the biography of Apollonius by Flavius Philostratos, a sophist connected with the court of Julia Domna, wife of emperor Septimius Sever. In the second part of this paper Apollonius’s unusual life is shown with an aim of evaluating which of the events reported in the sage’s biographies contain some element of historical truth and which are only implausible anecdotes. The third part of the article attempts to provide an answer to the question raised in the title. It seems that Apollonius of Tyana was neither a saint nor a charlatan in the Christian nomenclature but rather a figure who could be named theos aner (divine man) in the Hellenic(?) sense of this term. He was an eminentpagan holy man who throughout his entire life held intellectual discussions with Christians.